The Role of Knowledge Sharing to Improve the Quality of Human Resources - Zaenudin Tachyan; MLN. Rosmadi; Sri Maria Ulfha (Budapest International Research and Critics University, 2019)
This study aims to determine the role of knowledge sharing in order to improve the quality of human resources. The research method used is a qualitative method with a descriptive explorative approach. From the results of the research conducted, the results show that the quality of human resources can be increased not only through formal education but can also be done through knowledge sharing among fellow employees and also received support from management, especially related to motivation, appreciation, and career path. With the sharing of knowledge, it will increase innovation and creativity of employees so that production can be improved and have high competitiveness so that it affects consumers' interest in buying woven products produced by craftsmen in Majalaya, Bandung Regency.